Sex Differences in Rupture Risk and Mortality in Untreated Patients With Intact Abdominal Aortic Aneurysms - Mareia Talvitie; Malin Stenman; Joy Roy; Karin Leander; Rebecka Hultgren (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Studies on intact abdominal aortic aneurysms mainly focus on treated patients, and data on untreated patients are sparse. The objective was to investigate sex differences among untreated patients regarding rupture and mortality rates and to determine predictors for these events. Sex‐specific causes of death were evaluated. Methods and Results All patients ≥40 years diagnosed from 2001 to 2015 (n=32 393) with intact abdominal aortic aneurysms were identified in national registries; 60% (n=19 569) were untreated. Comorbid loads, crude rupture, and mortality rates were assessed. Predictors of 5‐year rupture and mortality were analyzed in Cox models (sex, age, comorbidities, income, and marital status). The proportion of men and women with multiple comorbidities was similar. Within 5 years, 798 ruptures occurred (9.7% women versus 6.9% men, P<0.001). Ruptures were independently predicted by female sex (hazard ratio [HR], 1.23; 95% CI, 1.07–1.42; P=0.004), chronic obstructive pulmonary disease (HR, 1.36; 95% CI, 1.15–1.62; P<0.001), age (HR, 11.49; 95% CI, 5.68–23.25 for ≥80 years; P<0.001), and income (HR, 0.63; 95% CI, 0.53–0.75 for highest tertile; P<0.001). After 5 years, 56.5% women and 50.4% men were deceased. Mortality was not independently predicted by female sex. Rupture was the third most common cause of death (11.9% women versus 8.7% men; P<0.001). The median time‐to‐events was 2.8 years. Conclusions A considerable proportion of patients with intact abdominal aortic aneurysms in surveillance remain untreated. Despite surveillance algorithms, the healthcare system fails to prevent a high number of ruptures, especially among women. The time‐to‐event data highlight the urgency to develop more individualized surveillance.